Environmental Abiotic Stress and Secondary Metabolites Production in Medicinal Plants: A Review - Venkatesha K.t.; Rc Padalıa; Arjita Punetha; Dipender Kumar; Priyanka Suryavanshi (Journal of Agricultural Sciences)
Medicinal plants that produce various secondary metabolites are quite useful to us owing to their anti-microbial properties, presence of huge amounts of anti-oxidants, cytotoxic nature, and various other medically significant properties. Medicinal plants, therefore, serve as raw materials for modern pharmaceutical medicines and several herbal medical supplements. Expansion and advancement of growing medicinal plants on large scale has flourished over the last few years. However, prolonged environmental changes have made medicinal plants susceptible to numerous abiotic stresses. On being exposed to abiotic stresses chiefly light (quality and quantity), extreme temperature conditions, water stress (drought or flooding), nutrients available, presence of heavy metals and salt content in the soil, medicinal plants undergo several changes physiologically and their chemical composition also gets altered. To combat the effects of abiotic stress, several mechanisms at morphological, anatomical, biochemical, and molecular levels are adapted by plants, which also include a change in the production of the secondary metabolites. However, plants cannot cope with extreme events of stress and eventually die. Several strategies stress such as the use of endophytes, chemical treatment, and biotechnological methods have therefore been introduced to help the plants tolerate the period of extreme stress. Moreover, nano bionics is also being developed as new technology to help plants survive stressful conditions.